Augmented Reality (AR) media-aided literature learning tool for elementary school students - Apriliya, Seni; Nuraeni, Weni; Nurjanah, Yeyen; Feri, Muhammad (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Learning devices need to be designed according to the characteristics of the material and be innovative. The results of the field study show that learning the subject of Indonesian fairy tale messages in elementary schools has not been fully implemented using such media, teaching materials, and assessment tools. Referring to this, this study aims to develop a literary learning device assisted by Augmented Reality (AR) media. This development research refers to the design-based research (DBR) development model from Amiel and Reeves (2008). The subjects of this development research trial were twenty students and a third-grade elementary school teacher. Data collection techniques used are semi-structured interviews, observation, and documentation. Data analysis is done by reducing, and presenting, until finding the interpretation of the data. The results of the study in the form of learning device products consisting of learning media, teaching materials, and assessment instruments showed that the Augmented Reality media-assisted literary learning device was validated as very feasible (85percent) with a high level of practicality category (93percent). The implication is that this product can be used in learning literature in elementary schools as an innovative alternative learning tool.